1996
DOI: 10.1177/000348949610500407
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Videostroboscopic Measurement of Glottal Gap and Vocal Function: An Analysis of Thyroplasty Type I

Abstract: The goal of surgical medialization of the vocal fold is to attain complete glottic closure. The purpose of this study is to quantify the glottal gap and to examine the relationship between glottal gap and vocal function perioperatively in thyroplasty type I. Glottal gap area was measured in 20 patients at the point of maximum closure of vocal fold vibration in digitized laryngeal stroboscopic images and was normalized by the square of vocal fold length. Glottal gap area thus measured was correlated with result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
87
0
5

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(95 citation statements)
references
References 16 publications
3
87
0
5
Order By: Relevance
“…Authors found a positive correlation between glottic area and breathy voice in unilateral vocal fold paralysis and confirmed that even only measurement of relative glottic space provides a direct assessment of glottic incompetence and objectively demonstrates the effect of surgical medialization (4,5).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…Authors found a positive correlation between glottic area and breathy voice in unilateral vocal fold paralysis and confirmed that even only measurement of relative glottic space provides a direct assessment of glottic incompetence and objectively demonstrates the effect of surgical medialization (4,5).…”
Section: Introductionmentioning
confidence: 75%
“…Measurements of actual size of pathological lesions and anatomical structures are of great clinical importance in practical medicine, as it provides objective additional information, which is crucially important for diagnostics, planning of treatment and assessment of outcomes of therapeutical or surgical management (4)(5)(6)14). On the other hand, in laryngology, these measurements are of great interest for scientific purposes revealing the impact of actual size of vocal fold mass lesions in pathogenesis of voice disorders and would be helpful elaborating automatic methods of image and voice analysis (9,15).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have mentioned the use of digitized stroboscopes for determining the phonatory gap, which may not be widely available. 13,14 As per our study, the gap can be measured with the help of a printout of a recorded white light image and a ruler. On analysis, if the phonatory gap is asymmetric, then the diagnosis of sulcus vocalis should be suspected, which should then be confirmed on stroboscopy.…”
mentioning
confidence: 99%